Actin dynamics in protein homeostasis. Issue 9 (30th September 2022) - Williams, Thomas D.; Rousseau, Adrien
Abstract: Cell homeostasis is maintained in all organisms by the constant adjustment of cell constituents and organisation to account for environmental context. Fine-tuning of the optimal balance of proteins for the conditions, or protein homeostasis, is critical to maintaining cell homeostasis. Actin, a major constituent of the cytoskeleton, forms many different structures which are acutely sensitive to the cell environment. Furthermore, actin structures interact with and are critically important for the function and regulation of multiple factors involved with mRNA and protein production and degradation, and protein regulation. Altogether, actin is a key, if often overlooked, regulator of protein homeostasis across eukaryotes. In this review, we highlight these roles and how they are altered following cell stress, from mRNA transcription to protein degradation.